Revitalisasi Perpustakaan Guna Meningkatkan Kualitas Literasi Mahasiswa : Revitalisasi Perpustakaan Guna Meningkatkan Kualitas Literasi Mahasiswa - zulkifli; Nofita Yanti; Sumiarti Sumiarti; Nora Afnita; Muhammad Rafi Ahadi; Hidayati Suhaili (Institut Agama Islam Sumatera Barat Pariaman, 2025)
The library holds a strategic role in enhancing students’ literacy, yet it is often underutilized. This study employs a qualitative research method with a case study approach to revitalize the library to be more appealing and functional for students. Data were collected through in-depth interviews, participatory observation, and documentation involving students, librarians, and lecturers. The findings indicate that the low utilization of the library is caused by outdated collections, uncomfortable reading spaces, and a lack of innovative services. The revitalization program included rearranging the reading space, digitizing references, and organizing literacy activities such as book discussions and writing workshops. After the revitalization, students showed increased reading interest and active participation in academic activities. Observations revealed a significant increase in weekly library visits, while interviews indicated that students felt more comfortable and motivated to access literacy resources. This study concludes that a library managed through a participatory and innovative approach can significantly improve students’ academic literacy. Therefore, a sustainable development strategy is essential to ensure that the library remains relevant and responsive to the academic needs of students in the digital era